Promoting Mental Health Education through Character Development - Hassine, Rajaa (International Journal of Language and Literary Studies, 2025)
In the 21st century, schools are increasingly called upon to address not only students’ academic achievement but also their mental well-being and moral growth. This shift responds to the rising concerns about mental health issues among students, which can manifest in violent behaviors, substance abuse, delinquency, academic failure, and school dropout. In the Moroccan educational context, mental health education remains underrepresented in school curricula, and character education is often overlooked as a means to address these challenges. This study aims to investigate how character education can contribute to mental health promotion through examining the influence of learning and practicing values on reducing negative student behaviors, and assessing how character modeling by teachers can enhance students’ social-emotional competencies. To achieve these objectives, a mixed-methods design was adopted, combining quantitative data from questionnaires administered to 450 students with qualitative data from semi-structured interviews with 40 teachers across secondary schools in diverse Moroccan regions. Quantitative data were analyzed using SPSS and AMOS, while qualitative data were processed with NVIVO. Findings reveal that character education significantly improves students’ mental health, fostering empathy, emotional regulation, social awareness, and self-management. Schools that actively promote character education report lower rates of aggression, absenteeism, and disengagement. However, the study identifies a lack of institutional support and structured teacher training as key barriers to effective implementation. The study concludes that integrating character education into school practices and teacher training programs offers a sustainable pathway to enhancing student well-being and advancing the quality of education in Morocco.